Non-Invasive Measurement of Cerebral Oxygen Metabolism in the Mouse Brain by Ultra-High Field 17O MR Spectroscopy. Issue 12 (December 2013) - Cui, Weina; Zhu, Xiao-Hong; Vollmers, Manda L; Colonna, Emily T; Adriany, Gregor; Tramm, Brandon; Dubinsky, Janet M; Öz, Gülin
To assess cerebral energetics in transgenic mouse models of neurologic disease, a robust, efficient, and practical method for quantification of cerebral oxygen consumption is needed. 17 O magnetic resonance spectroscopy (MRS) has been validated to measure cerebral metabolic rate of oxygen (CMRO2 ) in the rat brain; however, mice present unique challenges because of their small size. We show that CMRO2 measurements with 17 O MRS in the mouse brain are highly reproducible using 16.4 Tesla and a newly designed oxygen delivery system. The method can be utilized to measure mitochondrial function in mice quickly and repeatedly, without oral intubation, and has numerous potential applications to study cerebral energetics.